1977
DOI: 10.2307/1162336
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks for Comprehending Discourse

Abstract: Thirty physical education students and 30 music education students read a passage that could be given either a prison break or a wrestling interpretation, and another passage that could be understood in terms of an evening of card playing or a rehearsal session of a woodwind ensemble.Scores on disambiguating multiple choice tests and theme-revealing disambiguations and intrusions in free recall showed striking relationships to the subject's background. These results indicate that high-level schemata provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
5

Year Published

1983
1983
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 6 publications
(8 reference statements)
1
68
0
5
Order By: Relevance
“…Schema theory provided new and exciting developments in the field of cognitive psychology. The theory was used to explain and interpret a host of cognitive processes, such as inferencing, remembering, reasoning, and problem solving, and served as an impetus for a large volume of experimental research in learning, comprehension, and memory (e.g., Adams & Collins, 1979;Anderson, 1984;Anderson & Pearson 1984;Anderson, Reynolds, Schallert, & Goetz, 1977;Bloom, 1988;Bransford & Franks, 1971;Bransford & Johnson, 1972;McDaniel & Kerwin, 1987;Schallert, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Schema theory provided new and exciting developments in the field of cognitive psychology. The theory was used to explain and interpret a host of cognitive processes, such as inferencing, remembering, reasoning, and problem solving, and served as an impetus for a large volume of experimental research in learning, comprehension, and memory (e.g., Adams & Collins, 1979;Anderson, 1984;Anderson & Pearson 1984;Anderson, Reynolds, Schallert, & Goetz, 1977;Bloom, 1988;Bransford & Franks, 1971;Bransford & Johnson, 1972;McDaniel & Kerwin, 1987;Schallert, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that text comprehension is dependent upon prior knowledge (Anderson and Pitchert, 1978; Anderson, Reynolds, Schallert, and Goetz, 1977;Bransford and Johnson, 1973; Dooling and Lachman, 1971; Fass and Schumacher, 1981). Voss and his colleagues have provided a clear example of this in their research that describes how domain-specific knowledge influences reading (Chiesi, Spilich, and Voss, 1979;Spilich, Vesonder, Chiesi, and Voss, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The question that arises here is what should be taught to enhance comprehension. The comprehension processes literature shows that successful comprehension requires a reasonable competence in decoding (e.g., La Berge & Samuels, 1974), a match (to some extent) between background knowledge and the text information (Anderson, Reynolds, Schallert & Goetz, 1977) and the utilization of strategies that effectively select, store and retrieve information (Kirby, 1984).…”
Section: Reciprocal Teaching and Reading Comprehensionmentioning
confidence: 99%